2006
DOI: 10.1016/j.chemgeo.2005.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of Ni, Co and V between spinel-structured oxides and silicate melts: Importance of spinel composition

Abstract: 11Partitioning of Ni, Co and V between Cr-rich spinels and basaltic melt has been studied experimentally between 1150 and 1325 12 8C, and at controlled oxygen fugacity from the Co-CoO buffer to slightly above the hematite-magnetite buffer. These new results, 13 together with new Ni, Co and V analyses of experimental run products from Leeman [Leeman, W.P., 1974. Experimental 14 determination of the partitioning of divalent cations between olivine and basaltic liquid, Pt. II. PhD thesis, Univ. Oregon, 231-15 337… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
72
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(79 citation statements)
references
References 43 publications
5
72
0
2
Order By: Relevance
“…10 may reflect variations in D V spinel or the differences in the appearance of spinel and/or pyroxene as liquidus phases that co-crystallize with olivine. Righter et al (2006b) documented that whereas the D Ni spinel (≈10) and D Co spinel (≈5) are similar to olivine (and are not dramatically dependent on the composition of the early spinel or fO 2 ), D V spinel is dependent upon a range of variables (see equation #2 in Righter et al 2006b). Based on the observations of Righter et al (2006b), the Ni-Co trajectories as shown in Fig.…”
Section: Trace Element In Olivinementioning
confidence: 99%
See 1 more Smart Citation
“…10 may reflect variations in D V spinel or the differences in the appearance of spinel and/or pyroxene as liquidus phases that co-crystallize with olivine. Righter et al (2006b) documented that whereas the D Ni spinel (≈10) and D Co spinel (≈5) are similar to olivine (and are not dramatically dependent on the composition of the early spinel or fO 2 ), D V spinel is dependent upon a range of variables (see equation #2 in Righter et al 2006b). Based on the observations of Righter et al (2006b), the Ni-Co trajectories as shown in Fig.…”
Section: Trace Element In Olivinementioning
confidence: 99%
“…Righter et al (2006b) documented that whereas the D Ni spinel (≈10) and D Co spinel (≈5) are similar to olivine (and are not dramatically dependent on the composition of the early spinel or fO 2 ), D V spinel is dependent upon a range of variables (see equation #2 in Righter et al 2006b). Based on the observations of Righter et al (2006b), the Ni-Co trajectories as shown in Fig. 9 will not reflect the presents or absence of spinel during olivine crystallization because of the similarity of Co and Ni Fig.…”
Section: Trace Element In Olivinementioning
confidence: 99%
“…홍천 카 보나타이트와 포스코라이트 복합체의 자철석의 경 우 일부 시료를 제외하고는 Ti 함량이 적고(<0.1 wt.%), Mg와 Al 또한 상당히 낮은 조성을 보이면 서 기존 암체와는 다소 차이를 나타낸다. 일반적으 로 카보나타이트는 분화가 진행됨에 따라 자철석 의 Mg, Ti이 점차 감소하고, Al, Mn은 감소, 증가 혹은 일정하게 유지되는 경향을 보이는데 (Prins, 1972;Gaspar and Wyllie, 1983;Dawson et al, 1996;Chakhmouradian and Zaitsev, 1999;Karchevsky and Moutte, 2004;Lee et al, 2005) Sample HC10-11 HC10-6B HC10-6B HC10-6B HC10-6B HC10-6B HC10-6B HC10-6B HC10-6B HC10-6B HC0627 -19B HC0627 -19B HC0627 -19B HC0627 -19B HC0627 -19B HC0627 -19B HC0627 -19B Rock type P2 P2 P2 P2 P2 P2 P2 P2 P2 P2 P3 P3 P3 P3 P3 P3 (Horn et al, 1994;Toplis and Corgne, 2002;Righter et al, 2006;Reguir et al, 2008 Krasnova et al, 2004;Lee et al, 2004Lee et al, , 2005. 그러나 이제까 지의 연구결과 홍천 카보나타이트-포스코라이트 암체에서는 감람석이나 금운모의 산출이 보고된 바 없다 (Kim et al, 2001;Lee et al, 2002;Oh et al, 2010).…”
Section: 카보나타이트-포스코라이트 복합체의 분화unclassified
“…따라서 이들 광물의 부재나 자철석의 Mg, Al의 함량이 낮은 것은 연구지역 암체를 형성 한 모마그마가 원래부터 이들 원소들이 상당히 결 핍된 특성을 가졌음을 시사한다. Cr의 경우 Fe 3+ 에 잘 치환되는 성질을 갖는 원소이나 (Horn et al, 1994;Righter et al, 2006) 연구지역 자철석의 Cr 함량 이 적은 것도 카보나타이트와 포스코라이트가 결 핍된 모마그마로부터 생성된 것으로 해석할 수 있 다 (Kransnova et al, 2004;Reguir et al, 2008).…”
Section: 카보나타이트-포스코라이트 복합체의 분화unclassified
“…Consequently, crystallization of a spinel phase strongly influences the budgets of trace elements. The partitioning of elements between spinels and silicate melts is affected strongly by temperature (T ), oxygen fugacity (f O 2 ) and spinel composition (Righter et al, 2006), and may also be affected by pressure (P). Spinel geochemistry can, therefore, be used as an important tool in determining fractionation trends of magmas and the trace-element budget of primary basaltic magmas (Wijbrans et al, 2015), which gives insight into the source region of these melts in the mantle.…”
mentioning
confidence: 99%